VISUAL SYMBOLISM IN MAHA KUMBH AKHARA PROCESSIONS: EMBODIED PERFORMANCE OF SANATAN DHARMA - Umretiya, Gaurav R; Der, Sunil H (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Akhara peshwais at the 2025 Prayagraj Maha Kumbh grand processions of 13 akharas (7 Shaiva, 3 Vaishnava, 2 Udasin, 1 Sikh) embody Sanatan Dharma as kinetic epistemology, transforming Triveni Sangam’s chaos into eternal order for 50 crore pilgrims. Saffron-clad Nagas thunder forth, dhwaj snapping (Juna’s red Hanuman "Jai Shri Ram"), trishuls skyward, vibhuti-smeared torsos gleaming amid damru rhythms and jai tremors. These spectacles counter Western views of Kumbh as mere "world’s largest gathering," centering IKS where flags devour ahamkara, weapons channel shakti, and bodies map panchagni vidya. Jitenbharti’s wisdom "Tiger eats ego" positions sadhus as living shastra, bridging Ramcharitmanas devotion with performative moksha. Immersive ethnography triangulates participant observation (12 hours across three shahi snan: 29 Jan., 12/26 Feb.), 200+ Pixel 7a photographs (150 analyzed via Rose’s thematic coding), and 25 semi-structured Hindi/Gujarati interviews with Juna/Niranjani/Nirmohi sadhus (audio-recorded, NVivo-transcribed). Braun-Clarke thematic analysis (6 phases), IPA (Smith et al.), and narrative methods decode symbols; reflexive triangulation (Geertz) ensures sadhu co-creation. Spatial metrics (67% clustering), density shifts, grip evolution quantify ritual kinetics. Juna’s Hanuman dhwaj ripples sync chants (+40dB), drawing 3x women’s gazes, enacting ego-dissolution. Trishuls as shakti-vahak protect dharma, purifying via Ganga-dip. Vibhuti self-aligns post-snana into tri-shankha spirals/pentagrams, burning karma per Chandogya Upanishad. Sadhu testimony affirms peshwais as guru-parampara scrolls, fostering communitas. Decolonially, this reclaims Kumbh from logistics, proving embodied iconography teaches bhakti inclusivity women’s abir gestures mirroring Chandike.